An empathy lens into peer service providers - Shuqair, Saleh (2021)
Shuqair, S., Pinto, D. C., & Mattila, A. S. (2021). An empathy lens into peer service providers: Personal versus commercial hosts. International Journal of Hospitality Management, 99, 1-10. [103073]. https://doi.org/10.1016/j.ijhm.2021.103073 ---%ABS3% ---This paper was funded by Fundacao para a Ciencia e Tecnologia, Portugal. Funding number: DSAIPA/DS/0113/2019 Data Science and Over-Indebtedness: Use of Artificial Intelligence Algorithms in Credit Consumption and Indebtedness Conciliation in Portugal. Diego Costa Pinto. Universidade Nova de Lisboa (UNL).